LSR overexpression induces chemoresistance in triple negative breast cancer cells through MDR1 upregulation and apoptosis attenuation - Ming Zhao; Zhikun Ma; Amanda B. Parris; Xiaohe Yang (PLoS ONE, 2025)
Chemoresistance in breast cancer therapy, especially for triple negative breast cancer (TNBC) remains a significant challenge. Recent studies showed that overexpression of lipolysis-stimulated lipoprotein receptor (LSR), known as a tricellular tight-junction protein, was detected in TNBC and MDR1 was among LSR upregulated genes in a screening assay but its functional impact has not been studied. This study aimed to characterize LSR overexpression-induced regulation of MDR1 in TNBC cells focusing on chemoresistance. LSR was overexpressed in MDA-MB-231 cells and knocked-out via CRISPR/Cas9 in MDA-MB-468 cells for functional studies. Chemoresistance of individual cell lines was evaluated with doxorubicin treatment, followed by cell proliferation, invasion, colony formation and apoptosis assays. Modulated protein and mRNA levels of specific genes were assessed with Western blotting and RT-qPCR. MDR1 inhibitor verapamil and MDR1-targeted siRNA were used to evaluate the functional impact of LSR-induced MDR1. Overexpression of LSR not only promotes cell proliferation and invasion in MDA-MB-231 cells, but also renders the cells resistant to doxorubicin. LSR induces MDR1 expression at both mRNA and protein levels. Moreover, inhibition of MDR1 with specific inhibitor verapamil or MDR1 knockdown reversed cellular resistance to doxorubicin in LSR-overexpressing MDA-MB-231 cells. In contrast, knockout of LSR expression in MDA-MB-468 cells, which express higher levels of LSR, significantly sensitized the cells to doxorubicin-induced growth inhibition and apoptosis. Our data demonstrated that LSR overexpression promotes TNBC cell proliferation and invasion, and upregulation of MDR1 in these cells renders them resistant to doxorubicin, suggesting that targeting LSR could be a useful strategy to overcome chemoresistance in TNBC.